History in the Making: The Recognition of Moravian Church Settlements as a UNESCO World Heritage Site and Its Implications for Research in Moravian Studies - Vogt, Peter (Journal of Moravian history, 2024)
On July 26, 2024, the transnational site Moravian Church Settlements—comprising Bethlehem in Pennsylvania, Christiansfeld in Denmark, Gracehill in Northern Ireland, and Herrnhut in Germany—was inscribed on the UNESCO World Heritage List at the 46th meeting of the World Heritage Committee in New Delhi, India. The purpose of this article is to document this extraordinary event, to explain the background of the World Heritage inscription of Moravian Church Settlements, and to outline its implications for research in the field of Moravian studies. It is argued that while the World Heritage title for Moravian Church Settlements offers many opportunities and topics for Moravian studies, it is crucial for all interested scholars to understand the conceptual framework of Moravian Church Settlements from the Word Heritage perspective.